(untitled) (Eurasian Research Bulletin, 2023)
In the development of the modern education system, the teaching of various subjects creates the ability to apply new methods in practice. The implementation of flipped classroom technology in general secondary schools shows that the emergence of the flipped classroom links pedagogy and learning outcomes, and at the same time, may change future teaching and assessment. identifies gaps in the literature. In this technology, visualization is very important to better understand the structure of 2D and 3D objects with their projection. Thus, the flipped classroom is introduced and the students’ activities are monitored. The results showed that using a flipped classroom in a computer graphics course enhances student learning in an interesting way